Legislative Attention and Nonprofit Efficiency: A Link Across Sectoral Boundaries. - Ba, Yuhao; Berrett, Jessica; Coupet, Jason (Policy Studies Journal, 2026)
Government attention matters for nonprofit management and nonprofit‐government interactions. This study focuses on legislative attention, an important yet less‐studied aspect of government attention in public policy research, and examines its impact on nonprofit efficiency. By employing a longitudinal multi‐level regression design and utilizing data from state‐level legal proceedings and financial statements from a national sample of housing nonprofits, the findings suggest a positive impact of legislative attention on nonprofit efficiency, highlighting a complementary mode of nonprofit‐government relations. Additionally, this impact is more pronounced among nonprofits that receive government grants, suggesting the role of government support in enhancing nonprofits' responsiveness to government attention. Our study contributes to a macro–micro understanding of government‐nonprofit relationships and extends prior research on government attention by bridging the dynamics in the policy process with practices in other sectors.